Effectiveness of a theory-based intervention to improve postpartum type-2 diabetes mellitus screening uptake among women with gestational diabetes mellitus in Malaysia: a prospective quasi-experimental study - Minhat, Halimatus Sakdiah; Thangarajah, Puganeswary; Ahmad, Norliza (Universiti Putra Malaysia, 2024)
Introduction: Despite the importance of postpartum type-2 diabetes mellitus (T2DM) screening to ensure early detection and effective management of T2DM among women previously diagnosed with gestational diabetes mellitus, low uptake has been reported. In view of the proven effectiveness of theory-based interventions, this study aimed to evaluate the effectiveness of Information Motivation Behavioural Skills (IMB)-based intervention to improve postpartum T2DM screening uptake among pregnant women with GDM in Negeri Sembilan, Malaysia. Methods: A prospective quasi-experimental study was carried out among comparable respondents in the intervention and control groups, involving 61 and 55 respondents respectively. Validated and reliable self-administered questionnaire was used to measure pre- and post-intervention of knowledge, attitude and self-efficacy, based on the constructs of the IMB model, with postpartum T2DM screening uptake measured at 6-week postpartum. Results: The IMB-based intervention was effectively improved knowledge on gestational diabetes mellitus (GDM), and attitude as well as self-efficacy related to the screening, with significant difference in the 6-week postpartum T2DM screening uptake between the intervention and control groups. Between groups comparison revealed significantly higher mean scores for knowledge (ηp 2 =0.11), attitude (ηp 2 =0.031) and self-efficacy (ηp 2 =0.52) in the intervention group compared to the control group, with self-efficacy is showing the largest size effect. Conclusion: The IMB-based health intervention had effectively improved the 6-week postpartum T2DM screening among women with GDM in the intervention group, through the significant improvement of knowledge on GDM and attitude as well as self-efficacy related to the screening